POSTURAL HABITS AND AWARENESS, BALANCE, FLEXIBILITY, AND QUALITY OF LIFE IN WOMEN PRACTISING YOGA, PILATES, AND SEDENTARY CONTROLS: A CROSS-SECTIONAL STUDY - Leila Abdolalizadeh Khaselouei; Bahar Özgül; Eray Yüceel (Karya Journal of Health Science, 2026)
Objective: Despite the use of yoga and Pilates as health-promoting and preventive exercise approaches, there is a paucity of research investigating their effects on postural habits and postural awareness. This cross-sectional observational study aimed to compare the postural habits and awareness, along with balance, flexibility, and quality of life levels of adult females who regularly practice yoga and Pilates with those of sedentary individuals.Method: Females aged 20–40 who had never done yoga or Pilates before and had been practicing yoga (n=25) or Pilates (n=25) regularly for 3–6 months, and sedentary individuals who had and have not practiced such or any other exercises previously and currently (n=25) were recruited between December 2024 and October 2025. The level of postural habit and awareness was assessed using the Postural Habit and Awareness Scale, postural balance using the Y Balance Test, flexibility using trunk lateral flexion and sit-and-reach tests, and quality of life using the Nottingham Health Profile (NHP). Results: The demographic features of groups (age, height, body weight, and body mass index (BMI)) were statistically similar (p>0.05). The weekly frequency of practice was 2.37±0.93 (1–4) for the pilates group and 2.03±0.85 (1–4) for the yoga group. The postural habits sub-score in both the Pilates and yoga groups (p